KONSEP PENGELOLAAN KEUANGAN ISLAM MENURUT PEMIKIRAN ABU UBAID - khoirunnisa, ria; Ghozali, Mohammad (Universitas Muhammadiyah Prof DR HAMKA, 2018)
The State compiles a variety of planning that aims to realize the prosperity evenly. In the concept of BaitulMaal, it is a balanced budget. The concept that emphasizes the balance between the budget accepted by the budget issued. Thus, Islam allows the debtor but does not recommend. In the management of State finances, the Messenger as the leader is always trying to implement policies aimed at kemashlahatan of the Muslims. Abu Ubaid in Al-Amwal, who explained that the distribution of wealth in a fair and equitable should be based on the principles of good fiscal justice and perfect as possible. One of the biggest sources of funding over the financing of all government spending gained at this time is through taxes. In Indonesia, it is the backbone of the tax revenue of the State. Therefore, in order for tax not incriminating peng in the community than the Government of Indonesia to make related the poll rules. The existence of such a regulation is expected to appropriate tax proportional voting so that no one is harmed. Therefore, the Government of Indonesia sought to maintain the principle of fairness in the poll tax, namely by improving tax laws if found weaknesses in it. However, improvements for the sake of improvement Government Indonesia has done is not bearing fruit, even saw unfairly. So from this, it takes an alternative rule that can manifest justice in society. This research uses a type of research literature (library research) with the theoretical approach. This research study using the method of analysis and critique of the study research. This research using primary and secondary data. Methods of data analysis, using inductive techniques descriptive. The results of this research is the essence of thought Abu Ubaid on managing the finances of the State. This can be substantiated after review paradigm revenue from public ownership and State As like, sadaqah, kharaj, ' fa'i, ursy and khumus zakat, Jizya, and others that are tied to the halal-haram defined by Sharia law. Keywords: Management Of Public Finances Of Abu Ubayd, Baitul Maal